Natural Products in Renal-Associated Drug Discovery - Wasco Wruck; Afua Kobi Ampem Genfi; James Adjaye (MDPI AG, 2023)
The global increase in the incidence of kidney failure constitutes a major public health problem. Kidney disease is classified into acute and chronic: acute kidney injury (AKI) is associated with an abrupt decline in kidney function and chronic kidney disease (CKD) with chronic renal failure for more than three months. Although both kidney syndromes are multifactorial, inflammation and oxidative stress play major roles in the diversity of processes leading to these kidney malfunctions. Here, we reviewed various publications on medicinal plants with antioxidant and anti-inflammatory properties with the potential to treat and manage kidney-associated diseases in rodent models. Additionally, we conducted a meta-analysis to identify gene signatures and associated biological processes perturbed in human and mouse cells treated with antioxidants such as epigallocatechin gallate (EGCG), the active ingredient in green tea, and the mushroom Ganoderma lucidum (GL) and in kidney disease rodent models. We identified EGCG- and GL-regulated gene signatures linked to metabolism; inflammation (NRG1, E2F1, NFKB1 and JUN); ion signalling; transport; renal processes (SLC12A1 and LOX) and VEGF, ERBB and BDNF signalling. Medicinal plant extracts are proving to be effective for the prevention, management and treatment of kidney-associated diseases; however, more detailed characterisations of their targets are needed to enable more trust in their application in the management of kidney-associated diseases.